Analisis Penerapan Gri 3 Dan 11 Pada Laporan Keberlanjutan Perusahaan Migas Indonesia - Afni Putri Hairani; Anne Shofia Pratiwi; Cindy Fasabillah Putri (CV. ITTC INDONESIA, 2026)
The oil and gas industry has significant environmental and social impacts, requiring transparent and sector-relevant sustainability reporting. The Global Reporting Initiative (GRI) provides reporting standards through GRI 3 (Material Topics) and GRI 11 (Oil and Gas Sector Standard) to ensure disclosures reflect industry-specific risks. This study aims to analyze the level of compliance with GRI 3 and GRI 11 in the 2023 sustainability reports of upstream oil and gas companies and oil and gas service providers in Indonesia. A qualitative content analysis was conducted on sustainability reports from twelve companies listed on the Indonesia Stock Exchange, consisting of four upstream companies and eight supporting service companies. The results indicate that only a limited number of companies comply with GRI 3 requirements, while none explicitly apply GRI 11. Moreover, the findings reveal indications of symbolic compliance, characterized by narrative commitments without sufficient quantitative data and limited disclosure of sector-specific operational impacts. This study concludes that sustainability reporting practices in the Indonesian oil and gas sector have not yet fully achieved the substantive transparency objectives promoted by the GRI framework.